2019
DOI: 10.1111/mmi.14404
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus ArlRS two‐component system regulates virulence factor expression through MgrA

Abstract: The Gram-positive bacterium, Staphylococcus aureus, is a versatile pathogen that can sense and adapt to a wide variety of environments within the human host, in part through its 16 two-component regulatory systems. The ArlRS two-component system has been shown to affect many cellular processes in S. aureus, including autolysis, biofilm formation, capsule synthesis and virulence. Yet the molecular details of this regulation remained largely unknown. We used RNA sequencing to identify the ArlRS regulon, and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 93 publications
(165 reference statements)
4
54
0
3
Order By: Relevance
“…Expression of ArlR* activated the expression of 34 genes and downregulated the expression of 59 genes. The ArlRS regulon characterized by comparison of the wild type and its isogenic ArlRS mutant identified 250 genes differentially expressed (36). Forty percent of the genes regulated by ArlRS in our study were also differentially expressed in this study (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Expression of ArlR* activated the expression of 34 genes and downregulated the expression of 59 genes. The ArlRS regulon characterized by comparison of the wild type and its isogenic ArlRS mutant identified 250 genes differentially expressed (36). Forty percent of the genes regulated by ArlRS in our study were also differentially expressed in this study (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Genes affected by the NreBC TCS were extracted from reference 28 comparing the WT against a clean deletion mutant of nreABC grown under anaerobic conditions with or without nitrate. Genes affected by the ArlSR TCS are derived from reference 36 comparing the WT against a clean deletion mutant of either arlRS or mgrA . The published regulons were combined with the data obtained in this study and genes affected by at least one of the TCSs or phosphomimetic RRs indicated were included in the data set analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The thiol-based redox sensor Spx belongs to the arsenate reductase (ArsC) family, representing an unusual transcriptional activator lacking the HTH motif (Nakano et al 2003(Nakano et al , 2005Zuber 2009). In S. aureus, transcription of spx is positively regulated by the ArlRS two-component system (Crosby et al 2020). Spx is activated in response to oxidative stress by thiol oxidation of its CXXC redox switch motif to an intramolecular disulfide (Nakano et al 2005).…”
Section: Yjbh Adaptermentioning
confidence: 99%
“…MRSA virulence factor reporter assays. For reporter assays, overnight (ON) cultures of MRSA reporter strains (AH5116 46 , pCM29-PlukA, Cm R ; AH5382 46 , pCM29-PgehB, Cm R ; AH3613 47 , mgrA P2-sGFP fusion, Erm R ; AH5101 48 , Pnuc-sGFP, Cm R ; AH5095 46 , pCM29-PesxA, Cm R ) were prepared by sub-culturing 1:500 in fresh TSB (5% DMSO) with chloramphenicol (10 µg/mL) or erythromycin (5 µg/mL). Compounds 1-3 were resuspended in DMSO, and then diluted fresh in TSB for each assay replicate.…”
Section: Minimum Inhibitory Concentration Fraction 430f-f5 and Isolamentioning
confidence: 99%